2016
DOI: 10.1080/13880209.2016.1214740
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant efficacy of Kalanchoe daigremontiana bufadienolide-rich fraction in blood plasma in vitro

Abstract: Context: The main source of bufadienolides is toad venom; however, plants such as members of Kalanchoe Adans. (Crassulaceae) genus may also synthesize these bioactive substances. Objective: This is the first study on antioxidant effects and cytotoxicity of bufadienolide-rich fraction isolated from Kalanchoe daigremontiana Raym.-Hamet & H. Perrier. Materials and methods: The methanolic fraction was extracted from the plant roots and contained 0.48 mg bufadienolides/mg of dry mass (11a,19-dihydroksytelocinobufag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
(27 reference statements)
0
31
0
2
Order By: Relevance
“…It should be emphasized that earlier results, obtained by other authors in analogous experiments on different Kalanchoe plants indicated on significantly lower antioxidant efficacy of extracts, originated from different organs of Kalanchoe species (Sharker et al 2012 ; Quazi Majaz et al 2011a , b ). Furthermore, antioxidant action of the mentioned bufadienolide-rich extract of Kalanchoe daigremontiana was also confirmed using an experimental model of blood plasma exposed to peroxynitrite-induced oxidative stress (Kolodziejczyk-Czepas et al 2016 ).…”
Section: Biological Activity Of Kalanchoe Species-mentioning
confidence: 76%
See 1 more Smart Citation
“…It should be emphasized that earlier results, obtained by other authors in analogous experiments on different Kalanchoe plants indicated on significantly lower antioxidant efficacy of extracts, originated from different organs of Kalanchoe species (Sharker et al 2012 ; Quazi Majaz et al 2011a , b ). Furthermore, antioxidant action of the mentioned bufadienolide-rich extract of Kalanchoe daigremontiana was also confirmed using an experimental model of blood plasma exposed to peroxynitrite-induced oxidative stress (Kolodziejczyk-Czepas et al 2016 ).…”
Section: Biological Activity Of Kalanchoe Species-mentioning
confidence: 76%
“…Moreover, this group of compounds may be a base for development of new derivatives with enhanced antioxidant properties and decreased toxicity (obtained by chemical alterations of the pyrone moiety) (Aucamp 2014 ). Recent studies on bufadienolide-rich fraction of Kalanchoe daigremontiana roots demonstrated that its DPPH · scavenging ability was characterized by EC 50 = 21.80 μg/ml (Kolodziejczyk-Czepas et al 2016 ). Under the same experimental conditions, for the reference compounds, i.e.…”
Section: Biological Activity Of Kalanchoe Species-mentioning
confidence: 99%
“…Kalanchoe daigremontiana has anti-inflammatory, antimicrobial, antioxidant, and cytotoxic activities [9][10][11][12]. However, the effect of extracts of this plant on cancer cells was tested only on human lymphoblastic leukemia T cells (H9 and J45 cell lines) with estimation of inhibitory concentration values [11].…”
Section: Identification Of Flavonoids and Bufadienolides And Cytotoximentioning
confidence: 99%
“…Human blood buffy coats (from eight healthy volunteers) were purchased from the Regional Centre of Blood Donation and Blood Treatment in Lodz (Poland). The blood plasma samples were obtained by centrifugation according to previously described procedures [15]. All experiments were accepted by the committee on the Ethics of Research at the Medical University of Lodz RNN/347/17/KE.…”
Section: Antioxidant Activity In Human Plasma Modelmentioning
confidence: 99%
“…The concentrations of nitrated proteins were estimated from the standard curve of 3-nitrotyrosine-containing fibrinogen (3-NT-Fg) and expressed as the 3NT-Fg equivalents (in nmol/mg of plasma proteins). The concentration of free -SH groups in plasma samples was measured spectrophotometrically according to the Ellman s method, as described earlier [15], and -SH concentrations were expressed in µmol/mL of plasma. The TBARS levels were determined as described previously [16] and expressed in µmol TBARS/mL of plasma.…”
Section: Antioxidant Activity In Human Plasma Modelmentioning
confidence: 99%